PENGARUH RANAH AFEKTIF DAN KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI IPS DI SMA NEGERI 8 KOTA JAMBI - Kasiono, Tri Agung Wahyudi (Universitas Batanghari Jambi, 2019)
Abstract This study aims to determine the effect of the affective domain and emotional intelligence partially and simultaneously on student achievement in class XI IPS SMA Negeri 8 Jambi City. In this study, the authors used descriptive and verification research methods. The number of samples from both classes was 119 students. Based on the results of the study show that, (1) Affective Domain (X1) of 2,382 and t table of 1,987 from the comparison results, it can be seen that tcount is greater than ttable (tcount> ttable). Then H0 is rejected and Ha is accepted, meaning that there is an influence on the Affective Domain (X1) on Learning Achievement (Y) in Economics subjects in class XI IPS SMA Negeri 8 Jambi City. (2) Emotional Intelligence (X2) of 3,535 and ttable of 1,987, from the comparison results it can be seen that tcount is greater than ttable (tcount> ttable). Then H0 is rejected and Ha is accepted, meaning that there is an effect on Emotional Intelligence (X2) on Learning Achievement (Y) in economics class XI IPS at SMA Negeri 8 Jambi City. (3) From the research results it can be seen that the Fcount is 3,586 by comparing the Fcount with Ftable, with a significant level α = 0.05 (5%). It can be seen that the Fcount is 9,377 by comparing the F table α = 0.05 with the numerator free degree 2 and the denominator free degree 89, the F table is 3.04. Fcount greater than Ftable (9,377> 3.04) means that it can be said that there is an influence between Rana Afekti and Emotional Intelligence together (simultaneously) on Learning Achievement in Economic subjects in class XI IPS of SMA Negeri 8 Jambi City. Keywords : Ranah Afektif, Kecerdasan Emosional, Prestasi Belajar